Building Blocks on Corporate Governance in Public Companies (PCs) in Nepal: A Literature Review - Lamichhane, Basu Dev; Lama, Padam Bahadur; Hamal, Janga Bahadur; Karki, Murari (Journal of Balkumari College, 2024)
The purpose of this study is to review different corporate governance practices in Nepalese public companies and explore the corporate governance mechanisms through a review of literature consisting of theoretical and empirical reviews relating to Nepalese mechanisms and regulatory provisions. To meet this objective, the paper has adopted the descriptive with review research design. The study discloses areas of good governance attributes assessing their essentiality and effectiveness in governance mechanisms. The findings of the study reveal that internal control, control environment, monitoring activities through independent director, compliance with laws and regulations, training and development, transparency, board independence and competence, strong risk management processes and Chief Executive Officers (CEOs) and chairman role are the main attributes of corporate governance tool which enhances the long term shareholder value by the process of accountability of managers and by enhancing the firm’s performance for sustainability. The findings of the study might apply to the regulatory authorities, Public enterprises, Government, and Bank and Financial Institutions (BFIs).